Applicability of sulfate radical based advanced oxidation processes for drinking water treatment - Dilsizoğlu, Nergis (Graduate School, 2022)
The presence of organic matter in water is the most important factor affecting water quality. The effects of organic matter on conventional drinking water treatment plants have been investigated by researchers for many years. Organic matter in water cause undesirable problems in many cases such as color, taste and odor problem in drinking water systems, changing of microbiological quality negatively, necessity of additional treatment units etc. For this reason, organic matter removal is becoming more and more important day by day. The purpose of this study mainly supported by experimental works is investigation of the applicability of sulfate radical (SO4•−) based photochemical advanced oxidation processes (persulfate/UV-C and peroxymonosulfate/UV-C) in order to provide effective treatment (mineralization) of organic carbon that naturally found in raw water. In the first part of the thesis, experimental studies were conducted to examine the effects of the initial oxidant concentration on the process efficiency. The principles of application of the processes were determined on the basis of selected variables, considering the total organic carbon (TOC) removal efficiencies, residual oxidant concentration and alteration of UV254. The applicability of PS and PMS oxidants for TOC removal were compared by applying PS/UV-C and PMS/UV-C processes. In the second step of the study, it was aimed to determine the changing particle sizes during oxidation applications. Accordingly, PSD analyzes were performed on the raw water and the effluent sample of PS/UV-C and PMS/UV-C treatment processes. Therefore, treatment efficiency of each particle size was determined during oxidation processes. In raw water that come from a drinking water treatment plant with an original TOC concentration of approximately 5 mg/L, at the original pH of the solution (̴ 8.3) and an initial PS and PMS concentration of 0.1-1.0 mM range has been studied in order to specify the effect of initial concentration of oxidant on the mineralization processes. TOC, PS, pH and UV254 measurements are realized in the samples taken from specific time intervals (initial, 15th, 30th, 60th minute) during the reaction. According to the experimental studies, it was observed that organic carbon was effectively removed (55% and 64%) during the reaction time (60 minutes) by using both of PS/UV-C and PMS/UV-C photochemical advanced oxidation processes at an initial oxidant concentration of 1.0 mM and at pH 8.3. In addition, these results were confirmed by PSD analysis of raw and treated water by using PS/UV-C and PMS/UV-C processes. In sum, it was concluded that sulphate radical-based photochemical advanced oxidation processes can effectively remove organic carbon in natural waters under appropriate reaction conditions.
Sülfat radikali bazlı ileri oksidasyon proseslerinin içme suyu arıtımında uygulanabilirliği
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2022
Keywords: water treatment; su arıtma